Influence of Endo- and Exocyclic Heteroatoms on Stabilities and 1,3-Dipolar Cycloaddition Reactivities of Mesoionic Azomethine Ylides and Imines - Champagne, Pier Alexandre (J Org Chem, 2017)
The geometries, stabilities, and 1,3-dipolar cycloaddition reactivities of 24 mesoionic azomethine ylides and imines were investigated using density functional theory calculations at the M06-2X/6-311+G-(d,p)/M06-2X/6-31G-(d) level. The computed structures highlight how the commonly used "aromatic" resonance form should be replaced by two more accurate resonance structures. Stabilities of the dipoles were assessed by various homodesmotic schemes and are consistent with these compounds being nonaromatic. The activation free energies with ethylene or acetylene range from 11.8 to 36.6 kcal/mol. Within each dipole type, the predicted cycloaddition reactivities correlate with the reaction energies and the resonance stabilization energies provided by the various substituents. Endocyclic (X) heteroatoms increase the reactivity of the 1,3-dipoles in the order of O > NH ≅ S, whereas exocyclic (Y) substituents increase it in the order of CH(2) > NH > O > S. Distortion/interaction analysis indicated that the difference in reactivity between differently substituted 1,3-dipoles is driven by distortion, whereas the difference between azomethine ylides and imines is related to lower interaction energies of imines with the dipolarophiles.